PENGARUH PEMASARAN DIGITAL , KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KEMASAN DAN MINUMAN PADA PT. UNGGUL PLASTIK CEMANI SUKOHARJO - Yuli Poncowati; MG. Sukamdiani; Dian Noor Citra Perdana (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to determine and analyze the partial and simultaneous effects of digital marketing, product quality, and price on consumer purchasing decisions for food and beverage packaging products at PT. Unggul Plastik Cemani, Sukoharjo. Additionally, it seeks to identify the most dominant variable influencing these purchasing decisions. The research was conducted between December 2025 and January 2026. The study utilized a quantitative research design. The population comprised the consumers of PT. Unggul Plastik. Sampling was carried out using a non-probability purposive sampling method with the Lemeshow formula due to an unknown exact population size, resulting in a sample size of 100 respondents. Data collection techniques included documentation, direct observation, interviews, and questionnaires using a Likert scale. The data analysis methods employed descriptive statistics, instrument testing (validity and reliability tests), Multiple Linear Regression analysis, partial t-test, simultaneous F-test, and the coefficient of determination (R2) via SPSS 25 software. The operational indicators for the independent variables include website/platform quality, search engine optimization (SEO/SEM), online value proposition (OVP), content marketing, and social media marketing for Digital Marketing (X1) ; compliance with specifications, reliability, durability, and features for Product Quality (X2) ; and affordability, competitive pricing, price-to-quality alignment, transparency, and price-to-benefit alignment for Price (X3). The dependent variable, Purchasing Decision (Y), is measured through need recognition, information search, evaluation of alternatives, purchase execution, and post-purchase behavior. The results are expected to prove the formulated hypotheses that digital marketing, product quality, and price have a significant positive effect on purchasing decisions both partially and simultaneously, with product quality hypothesized as the most dominant factor influencing consumer buying choices at PT. Unggul Plastik Cemani, Sukoharjo. Keywords: : Digital Marketing, Product Quality, Price, Purchasing Decision, Packaging Products.